Blackbox Testing on Web Based Capstone Project Information System in Electrical Engineering Study Program Udayana University - Semara Putra, Anak Agung Made; Permana, I Wayan Guna; ER, Ngurah Indra; Purnama, Fajar; Sri Utami, Ni Komang; Sukadarmika, Gede (Journal of Electrical, Electronics and Informatics, 2025)
Capstone Project Information System is an information system developed to handle administrative processes related to capstone project activities in the Electrical Engineering Study Program at Udayana University. With this information system, it is expected to minimize inefficient repetitive work and reduce the potential for human error in the implementation of capstone projects. To ensure that the Capstone Project Information System can work properly in handling capstone project administration in the Electrical Engineering Study Program at Udayana University, blackbox testing is carried out, where the focus of this test is on system input and output without paying attention to the internal structure of the program code. Based on the results of blackbox testing on six user roles in this information system, it can be concluded that this system has successfully met the functional needs of various types of users. The features that have been made work well, indicating that the Capstone Project Information System has met the expected functionality criteria, indicating that this system has been well designed.